Covid-19: Influence on academic and personal lives of medical students - Ahmed, Sanaa; Raza, Syeda Zareen; Raes, Zunaira; Saleem, Saad (Journal of Pakistan Psychiatric Society, 2021)
The pandemic of covid-19 caught the world unprepared. Not only the panic and chaos overtook even the strongest of the nations but also had a large number of casualties and deaths. The long-term effects have yet to be found out but immediately included financial crisis, depression, anxiety and social isolation. The lockdown globally opened a new window to online education and work from home trends. Many people lost their jobs. It also brought opportunity to people by selling products online.The aim of the study was to find out the effects of the pandemic on the lives of the medical and allied studying at a government-based institution in Pakistan.Study design was descriptive cross sectional and convenience sampling was done. Sample size of 310 students was calculated from 5 institutes of Jinnah Sindh Medical University. After taking permission from IRB and institutional head, students were emailed the forms which contain the consent and the questionnaire to be filled on google form.Our results are consistent with the findings of others related to the effects of the Covid-19. Students reported lack of physical activity, sleep deprivation, alteration in sleeping habits, depression and social isolation. They also reported their satisfaction with their online learning experience as bad and complained about the increase in workload.ConclusionsOur findings are consistent with the previous studies. This study is different from previous ones as we have looked at all the aspects of student`s life while previous ones mainly highlighted a single side either academics, or social or mental health. It is suggested that counselling services be provided to students to help them cope with these effects.